Screening of antifungal compound producing bacteria from piper nigrum farm against phytophthora capsici - Toh, Seng Chiew (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Piper nigrum, also known as the black pepper, is one of the important spice crops that is highly demanded by the world market population. It is widely used in cuisines, aromatherapy and medical. However, the infection by the Phytophthora capsici has caused the severe crop loss to the farmers and decrease in the economic values of black pepper. In order to control the growth of these pathogenic fungi, chemical fungicides such as Bordeaux mixture and copper oxychloride are widely used. However, these chemicals can cause pollutions to the environment and eliminate the non-targeted species such as the growth promoting bacteria in the soil. Therefore, the aim of this research is to isolate the endophytic bacteria that live within the roots of plants which can produce the antimicrobial compound against the growth of Phytophthora capsici. In this research project, root samples were collected from the Piper nigrum farm and the bacteria isolates were screened for their antagonistic effect via dual culture assay, mycelial growth test, spore germination test and double plate assay. Then, three bacteria showing antagonism towards Phytophthora capsici were characterized by using Polymerase Chain Reaction (PCR) and 16S rRNA sequencing. These bacteria isolates were identified as Enterobacter cancerogenus, Enterobacter cloacae P 101 and Enterobacter asburiae LF7 a by using Basic Local Alignment Search Tool (BLAST) via National Center for Biotechnology Information (NCBI).